Assessment of Farmers' Knowledge, Attitudes and Practices on Antibiotics and Antimicrobial Resistance - Ozturk, Yasin; Celik, Senol; Sahin, Emre; Acik, Mehmet Nuri; Cetinkaya, Burhan (Mdpi, 2019)
Simple Summary Antibiotic resistance is a global problem that threatens human and animal health and has increased in recent years. Although many factors are responsible for the development of resistance, antibiotics used in animals for preventive, therapeutic, and other purposes play a major role. Conscious and rational antibiotic use in animals will contribute to decreases in resistance. It is therefore important to determine knowledge, attitudes, and behaviors of farmers working in the livestock sector with regard to antibiotic knowledge, use, and resistance in order to develop communication strategies accordingly. The aim of this study was to measure the knowledge of livestock farmers about antibiotics by conducting a questionnaire survey. As a result of the survey, it was found that knowledge of the participants on antibiotics and resistance was very low. It was concluded that periodic training programs can be employed to overcome this problem and raise awareness among farmers. The aim of this study was to determine knowledge, attitudes, and behaviors of farmers dealing with animal husbandry in eastern Turkey with regard to antibiotic knowledge, use, and resistance. A face to face questionnaire survey, consisting of five sections with 42 questions in total, was applied to 360 farmers located in the region. The questions in the first and fifth sections were closed-ended while those in other sections were prepared using the Likert scale. It was determined that knowledge of the farmers about antibiotic use, duration, storage, and resistance was well below desired levels. This was particularly remarkable in the participants with a low level of education, living in rural areas, and those at 48 years of age or over. In contrast, younger and highly educated participants living in urban areas were more knowledgeable about antibiotic use and they were well aware of the fact that resistance might pose a great risk for public health. Providing appropriate antibiotic use in animals through systematic training of livestock farmers is crucial in tackling the resistance problem.
Keywords: antibiotic use; antibiotic knowledge level; antibiotic resistance; farmers; survey; questionnaire